Pandangan Dunia Modern dan Islam tentang Ilmu Pengetahuan - Samiuddin, Lalu Muhammad (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2023)
God's creation of something in pairs, it seems that it is not sufficiently understood up to the limits of the creation of creatures. It seems that this covers all sides, everything in this world, including differences in views about things. The same goes for different views on science. Science does not stop at a religious point of view (in this case purely Islamic), but also gets a 'spotlight' from the modern world, which is rooted in philosophers who spend the rest of their lives thinking.